Buckling suppression of a cantilever structure with a modified fuzzy sliding mode control - Jianhua Pan; Lin Sun; Xiaopei Liu; Yuyuan Zhang; Yili Duo (Scientific Reports)
Abstract Based on fuzzy sliding mode control, a control strategy is developed for the buckling suppression of a cantilever structure. Due to the laminated composite structure, shear effects on the dynamic behavior of the structure are incorporated into the development of the equations of motion. Subsequently, a second-order Galerkin discretization is applied to establish a two-dimensional nonlinear system for the cantilever structure. Numerical simulations demonstrate that a two-dimensional nonlinear dynamic model of the laminated composite structure is essential for precise buckling vibration estimations. Therefore, a new active control strategy for large-amplitude buckling suppression of a two-dimensional nonlinear dynamic system of a cantilever beam is established and implemented, effectively suppressing the large-amplitude buckling response in numerical studies.